Consumer Knowledge of Organic Poultry Meat Foods. Survey Studies - Kęsiak, Monika; Lesiów, Tomasz (Wiedza konsumentów dotycząca żywności ekologicznej z mięsa drobiowego. Badania sondażowe, 2025)
Aim: This study aimed to determine the level of consumers’ knowledge of organic food from poultry meat. Methodology: A survey was conducted in 2024 among 100 respondents. Results: The respondents showed an average level of knowledge about the benefits of organic poultry. When making purchasing decisions, they were not always guided by certificates or organic labels and more often took into account the brand of the product, the localness of the source, and the health and taste qualities of the meat. Concerns about quality, safety, and environmental sustainability still challenge producers and distributors. The respondents often obtained information about organic food from the Internet, personal experience, and recommendations from family and friends. Implications and recommendations: Education and consumer awareness, therefore, play a key role in shaping preferences and purchasing decisions. There is a need for further educational and informational activities, both on the part of producers and distributors, as well as academic and social institutions, to support the development of the organic poultry meat market and meet consumers’ growing expectations. Originality/value: It is the first time a survey has been concerned with poultry meat products, compared with literature surveys concerned with all organic foods.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2025, Nr 41, s. 13-22